Postoperative in general surgery: Analysis of a series of 200 successive operations - Praderi, Raúl; Coiro, Miguel; Cassinasco, Angeles; Vignoli, Elena; Terra, Eneas; Montano, Teresa (Cirugía del Uruguay, 1993)
The authors present statistics of 206 surgical procedures which were performed in 200 operations in 195 general surgery patients by the same surgical team at one institution. 178 majar and complex surgery operations were performed.